(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to analyze the influence of visionary leadership of the school principal and Self efficacy on the performance of teachers in public elementary schools in Batang Cenaku District. The research method used is a survey with a quantitative approach, and regression analysis. The sample consists of 152 teachers selected from all public elementary schools in Batang Cenaku District. Data were collected through closed-ended questionnaires and analyzed descriptively and inferentially using Microsoft Excel and SPSS version 26. The results show that the visionary leadership of the school principal and Self efficacy have a significant impact on teacher performance. Partially, visionary leadership has a regression coefficient (?) of 0.483, which means that an increase in visionary leadership will improve teacher performance by 0.483 units, with a t-value of 8.141 (p < 0.05). The contribution of this variable to teacher performance is 30.1%. Additionally, Self efficacy also significantly influences teacher performance, with a regression coefficient (?) of 0.433, indicating that an increase in Self efficacy will improve teacher performance by 0.433 units (t-value 7.459, p < 0.05) and contributes 27.1%. Simultaneously, both variables significantly influence teacher performance, with an F-value of 94.410 (p < 0.05) and a coefficient of determination (R²) of 0.559, which means that together they explain 55.9% of the variation in teacher performance. These findings emphasize the importance of visionary leadership and self-confidence in enhancing teacher performance in elementary schools.